2020
DOI: 10.1002/fsn3.1627
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grape seeds on wine composition and astringency of Tempranillo, Garnacha, Merlot and Cabernet Sauvignon wines

Abstract: Background The aim of this work was to study the influence of grape berry morphology, especially the seed weight percentage, on the tannin concentration and astringency of red wine. Clusters of Tempranillo, Garnacha, Merlot, and Cabernet Sauvignon were characterized and their seeds were extracted and macerated in a model wine solution. In parallel, we elaborated three types of wines of each cultivar. One wine was made with only grape juice, one wine was made adding the appropriate proportion of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
(68 reference statements)
2
20
0
Order By: Relevance
“…Higher pH values (Mostar, 3.65 and 3.70) are relatively in line with the statements of other authors [ 57 , 71 ]. The high values of TSS in the grape juice of the Merlot variety at both analyzed localities in the years of the research are relatively in line with the results of some other authors [ 63 , 72 , 73 ], while the level of determined titratable acids (TA) was mostly insignificantly higher compared to the results of the same authors. Higher values of TSS (24.0 °Brix and 24.4 °Brix) in Trebinje were observed during research on the grape quality of this variety in the earlier period (2016–2017) [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher pH values (Mostar, 3.65 and 3.70) are relatively in line with the statements of other authors [ 57 , 71 ]. The high values of TSS in the grape juice of the Merlot variety at both analyzed localities in the years of the research are relatively in line with the results of some other authors [ 63 , 72 , 73 ], while the level of determined titratable acids (TA) was mostly insignificantly higher compared to the results of the same authors. Higher values of TSS (24.0 °Brix and 24.4 °Brix) in Trebinje were observed during research on the grape quality of this variety in the earlier period (2016–2017) [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…Cultivation of the Merlot variety in different agroclimatic conditions significantly affects the specific characteristics of the bunch, which are characterized by a slightly smaller number of berries in the bunch [ 62 , 63 ] or their size [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that berry size and seed content is determinant of flavan-3-ols content in red wines. In this sense, Merlot grapes are characterized by a small berry size and high seed content that may lead to the high concentration of flavan-3-ols into the wine [ 39 ]. Table 2 describes the content of flavan-3-ols in WC.…”
Section: Resultsmentioning
confidence: 99%
“…Canals et al (2008) revealed the positive relationship between seed presence and wine anthocyanin content, and also showed a correlation with wine astringency and bitterness. The total concentration of seed phenolics in wine was related to increased wine bitterness, but not astringency (Arnold & Noble, 1978), however, more recent work showed that cultivars having a greater proportion of seed weight to berry weight produce more astringent wines (Gombau et al, 2020). Additionally, high concentrations of seed phenolics mask desirable wine aromas (Bautista-Ortín, Busse-Valverde, López-Roca, Gil-Muñoz, & Gómez-Plaza, 2014; Cliff, Stanich, Edwards, & Saucier, 2012; Parker et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ćurko et al, 2014;Gombau et al, 2020;Narukawa et al, 2010). Flavan-3-ol monomers are also well known to impact bitterness in wine(Sáenz-Navajas et al, 2015)…”
mentioning
confidence: 99%